Perubahan Nilai Debris Indeks melalui Penyuluhan Media Leaflet dan Fliphart Siswa Kelas 5 SDN I Perumnas Way Halim Bandar Lampung - Desi Andriyani (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Development in the field of dental and oral health is one part of overall health development which has a great responsibility for increasing the value of dental and oral health in the community. Efforts to overcome dental and oral health problems must be based on a good understanding of the knowledge that affects the dental and oral health of the community, both health workers as service providers and the community as users of available services. Print media or Leaflets and Flipcharts are media used in counseling The purpose of this study is to determine the description of the success of counseling using leaflet and flipchart media on the value of debris index for students in grades 5A and 5B at SDN I Perumnas Way Halim Bandar Lampung. This type of research is descriptive and correlational research. The research was conducted at SDN I Perumnas Way Halim, Bandar Lampung. The population in this study were students in grades 5A and 5B at SDN I Perumnas Way Halim Bandar Lampung, totaling 80 people. with a population of 80 people as a sample. The variables used in this research are Leaflet and Flipchart media. Based on the research that has been done, it was found that the DI criteria before counseling was carried out using Leafet 1.12 (medium) and Flipchart 1.19 (moderate) media. while the DI criteria after counseling using Leaflet media is 0.03 (Good) and Flipchart is 0.02 (Good) then there is a decrease in DI value before and after counseling using Leaflet and Flipchart media